Thoroughly grasping the viewpoints of the 13th Party Congress on protecting sovereignty over sea and islands in the new situation - Bùi Quang Huy; Lê Văn Hòa (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Under the leadership of the Party, the management role of the State, promoting the strength of unity of the whole nation, we are determined to firmly protect the sacred sovereignty of the sea and islands of the Fatherland. Currently, the task of protecting the country's sovereignty over seas and islands has been facing great difficulties and challenges. The article thoroughly grasps some basic contents in the document of the 13th Party Congress on protecting sovereignty over sea and islands in the new situation.